Łokieć tenisisty - czy jest to tylko problem lokalny? = Tennis elbow - is it only a local problem? - Siedlaczek, Marcin; Siedlaczek, Aleksandra; Srokowski, Grzegorz; Srokowska, Anna; Kowalik, Tomasz; Radzimińska, Agnieszka; Bułatowicz, Irena; Zukow, Walery (Journal of Education, Health and Sport, 2015)
Siedlaczek Marcin, Siedlaczek Aleksandra, Srokowski Grzegorz, Srokowska Anna, Kowalik Tomasz, Radzimińska Agnieszka, Bułatowicz Irena, Zukow Walery. Łokieć tenisisty - czy jest to tylko problem lokalny? = Tennis elbow - is it only a local problem? Journal of Education, Health and Sport. 2015;5(12):535-543. eISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.42267 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A535-543 http://pbn.nauka.gov.pl/works/686293 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 10.12.2015. Revised 15.12.2015. Accepted: 29.12.2015. Łokieć tenisisty - czy jest to tylko problem lokalny? Tennis elbow - is it only a local problem? Marcin Siedlaczek1, Aleksandra Siedlaczek1, Grzegorz Srokowski1, Anna Srokowska2, Tomasz Kowalik2, Agnieszka Radzimińska1, Irena Bułatowicz1, Walery Zukow3 1. Uniwersytet Mikołaja Kopernika w Toruniu, Collegium Medicum w Bydgoszczy, Katedra Fizjoterapii, Bydgoszcz, Polska 2. Uniwersytet Mikołaja Kopernika w Toruniu, Collegium Medicum w Bydgoszczy, Katedra i Zakład Podstaw Kultury Fizycznej, Bydgoszcz, Polska 3. Uniwersytet Kazimierza Wielkiego w Bydgoszczy, Bydgoszcz, Polska Correspondence: mgr Marcin Siedlaczek ul. Monte Cassino 55 85-791 Bydgoszcz tel. 604631227 Marcinsied@o2.pl Streszczenie Łokieć tenisisty jest jedną z najczęstszych dolegliwości rozpoznawanych w obszarze stawu łokciowego. Pomimo tak powszechnego występowania wiele pytań związanych z tą jednostką pozostaje niewyjaśnionych. Doniesienia dotyczące efektywności różnych form terapii również zdają się być niejednoznaczne. Celem pracy jest przybliżenie globalnych zależności występujących w ciele, które mogą wpływać na dolegliwości pacjentów oraz próba odpowiedzi na pytanie, czy zawsze należy szukać przyczyny w miejscu bólu. Zwrócić uwagę należy na fakt, iż współczesna anatomia bardziej dzieli niż łączy, a co za tym idzie często pośrednie i bezpośrednie zależności pomiędzy nawet blisko położonymi strukturami są w badaniu czy analizie pomijane. Abstract Tennis elbow is one of the most common disorders diagnosed in the elbow area. Despite such prevalence, lot of questions associated with this disease still remains unexplained. Reports about the effectiveness of treatment also seems to be not clear. The aim of the work is to familiarize with global relationships in a body, that can influence the disorders of patients and attempt to answer the question of whether we should always look for the pain cause in painful localization. We should pay attention to the fact, that classic anatomy divides rather than connect. Because of this fact, therapists often ignore direct and indirect relationships between even closely located structures. Słowa kluczowe: łokieć tenisisty, powięź. Key words: tennis elbow, fascia.